2013
DOI: 10.1007/s00228-013-1527-3
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of thiopental with esomeprazole in critically ill patients

Abstract: Based on these results, we conclude that concomitant administration of esomeprazole increases the volume of distribution and the half-live of thiopental. This drug-drug interaction should be considered when a target concentration has to be reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For example, the proton-pump inhibitor Esomeprazole is frequently prescribed in critically ill patients. It has been reported that prescribing Esomeprazole increases the volume of distribution and half-life of Thiopentone, which needs to be taken into account when aiming for certain target concentrations [ 50 ].…”
Section: Pitfallsmentioning
confidence: 99%
“…For example, the proton-pump inhibitor Esomeprazole is frequently prescribed in critically ill patients. It has been reported that prescribing Esomeprazole increases the volume of distribution and half-life of Thiopentone, which needs to be taken into account when aiming for certain target concentrations [ 50 ].…”
Section: Pitfallsmentioning
confidence: 99%